Binding of Basic Dyes by the Algae, Chara aspera - Low, K. S.; Lee, C. K.; Toh, B. L. (Universiti Putra Malaysia Press, 1994)
Non-living biomass of the algae Chara aspera is capable of binding two basic dyes, methylene blue and basic blue 3, from aqueous solution. Factors such as dye concentration, contact time, sorbent dosage and pH of solution were studied. Maximum sorption capacities of the algae for methylene blue and basic blue 3 are 139.4 and 17.8 mg/g, respectively, as determined from the Langmuir isothenns.